Improving Lake Water Clarity by Cultivation of Water Hyacinth (Eichornia crassipes) - Mursalin; Achmad Hizazi; Nazarudin; Agus Subagyo (Jurnal Penelitian Pendidikan IPA, 2025)
Research on the use of water hyacinth (WH) to improve the quality of polluted water has been widely reported, but discussions on the ability of WH to clear turbid water are still rare. This research examines the possibility of using WH as a natural clarifier for Lake Bata. Treatments with 3 variations in the percentage of lake closure with WH cultivation (25, 50, and 75%) were applied for 40 days with 3 repetitions. Water quality and turbidity measurements were carried out every 4 days. The data was analyzed descriptively in graphical form to see a model of these changes. It was found that the pollutants Fe, Hg, nitrate, phosphate and ammonia were present in very small and safe quantities, but the water turbidity level did not meet the standards of the Indonesian Minister of Health yet. During the WH growth, the turbidity decreasing follows the equation Y(25) = - 0.114x + 28.52; Y(50) = -0.195x + 29.83; and Y(75) = -0.235x + 30.14 for cover percentages of 25, 50 and 75% respectively, where y for the turbidity (NTU) and x for WH growth time (days). To meet turbidity standards, WH coverage percentages of 25, 50, and 75%, require cultivation periods of 32, 28, and 24 days, respectively.